The moderating effect of the internal ownership on the relationship between the effectiveness of Board of Directors and Executive Compensation with earnings management in the Amman Stock Exchange
The primary goal of this study is to determine the level of earnings management (EM) practices in Jordanian capital market and the effectiveness role of the corporate governance in mitigating these practices especially after adopting the Jordanian corporate code in 2009. Therefore, this study revisits the literature on the relationship between the factors of the effectiveness of the board of directors at the individual level and as a bundle through creating a score of effectiveness for nine board of directors factors. This study also investigates how the effectiveness of board of directors and the executive compensations are moderated by internal ownership “managerial and family ownership” to mitigate EM. In this term, four theories formed the theoretical foundation of this study. The agency theory, the resource dependence theory and the positive accounting theory predict that corporate governance practices would play an important role in improving the financial reporting through the monitoring role, resource dependence role and ability to combining the interest of the contractual parties. However, the institutional theory refers to the possibility that these practices can be as an imitation for the market “isomorphism” and social pressure then achieve the desired regulation. Most of the prior studies focused on the traditional interaction among corporate governance mechanisms and EM, thus, neglected the variance of these practices that can be attributed to the business environment and the nature of ownership structure. Consequently, this study sheds light on whether the central or traditional agency problem existed. Moreover, to achieve the objectives of this research Kothari et al. 2005 model is used as a proxy of EM. Three models were developed and tested to answer the research questions. These models were tested using the panel data analysis methods over a sample of 798 firm-observation collected from the Jordanian nonfinancial firms listed in the ASE during the period of 2009-2015. The findings of the first model (Random-effect) provides each of the board independence, meeting frequency, CEO duality, audit committee, directors tenures and the executive compensations significantly affect the EM practices.